The Philippines v. China Jurisdictional Award and its Implications for the Republic of Korea - Feron, Henri (Columbia Journal of Asian Law, 2016)
The Philippines v. China jurisdictional award seemingly challenged the rule that third party fora cannot assume jurisdiction in the context of a territorial dispute without the consent of all parties involved. The present paper analyzes the decision and identifies its implications for the Republic of Korea in territorial disputes with its Chinese, Japanese and North Korean neighbors. It finds that Philippines v. China, far from undermining the South Korean position in these disputes, could actually benefit it against Japan.